Relevant Historical Cases Showing Advertising Cultural Impact - Montero, Mercedes (2022)
The aim of this paper is to discuss some concrete examples of the influence of commercial communication in decisive processes and events of the recent history. We endeavour to show that the training of future professionals should not be confined to purely technical and economic aspects of the world of advertising, but should also include deeper consideration of the cultural impact of the persuasive forms of communication. This will greatly enrich the teaching of our subject, as we come to focus on their influence within the mesh of social, cultural, political and other trends that make up the world today. This will mean that courses that might otherwise be overly technical are given a humanistic dimension.